Touring China : a history of travel culture, 1912-1949 - Mo, Yajun, 1980- (Histories and cultures of tourism., 2021)
"Charts the development of domestic tourism and the maturation of a nationalist travel culture in the first half of the twentieth century. Drawing on a wide range of sources including unpublished business archives, organization newsletters, bulletins from transportation companies, popular newspapers and magazines, and guidebooks, this book puts tourism and popular travel culture at the center of China's transition from empire to nation-state"--